HUBUNGAN PENGETAHUAN DENGAN SIKAP REMAJA PUTRI TERHADAP DISMENORHEA DI MTS AL FAAIZUN WATANG PALAKKA KABUPATEN BONE TAHUN 2024 - Sumarni, Sumarni; Susilawati, Susilawati (Yayasan Nusantara Hasana Berdikari, 2025)
This study discusses the Relationship between Knowledge and Adolescent Girls' Attitudes Towards Dysmenorhea at Mts Al Faaizun Watang Palakka, Bone Regency in 2024, This study aims to determine the relationship between knowledge and adolescent girls' attitudes towards dysmenorhea at MTs Al Faaizun Watang Palakka, Bone Regency. The research method used is an analytical survey with a cross-sectional approach. The sample of this study is 50 young women selected through the purposive sampling. The results of the study showed that there was a significant relationship between the level of knowledge and attitudes of adolescent girls towards dysmenorhea in Mts Al Faaizun Watang Palakka, Bone Regency. Adolescents who have high knowledge about dysmenorhea tend to have a more positive attitude in dealing with the condition. In contrast, teenagers with low knowledge tend to have a negative attitude. This study concludes that knowledge plays an important role in shaping young women's attitudes towards dysmenorhea. Therefore, it is recommended to increase reproductive health education among adolescents in order to reduce the negative impact of dysmenorrhea.